PDAM WATER QUALITY EVALUATION OF PHYSICAL, CHEMICAL AND BIOLOGICAL PARAMETERS IN MANJANGLOE VILLAGE, TAMALATEA SUB-DISTRICT, JENEPONTO DISTRICT - Fitriani Kahar (Jurnal Riset Kesehatan, 2019)
Water is the most important human need. The problem that arises in the Jeneponto district is the PDAM water that is used daily by the community is turbid, smelly, and often causing an itchy effect on the skin. This research is a type of observational study with a descriptive approach and laboratory test because the aim is to describe or describe the state of water quality of PDAM in terms of physical parameters, chemical parameters, and biological parameters in Kelurahan Manjangloe Kecamatan Tamalatea Kabupaten Jeneponto. The population and sample in this study is clean water from all PDAM taps received by the community in Manjangloe village Tamalatea Sub-district Jeneponto District. The results obtained from the physical parameters, there are 10 samples (100%) that meet the requirements, while the biological parameters there are 6 samples (60%) that meet requirements, while for chemical parameters there were 7 pH (70%) qualified parameters for checking water, while for the remaining chlorine water inspection parameters it was found that 0 samples (0%) were eligible. Suggestions the local PDAM should continue to maintain, improve, and monitor the quality of clean water both in the outlet pipe and the water that is distributed to customers.